(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Endometrial carcinoma is one of the most common gynecologic malignancy and main prognostic factors are depth of myometrial invasion & lymph node metastasis. Diffusion Weighted MR Imaging at high b value enhances natural contrast between tumor & background normal tissues. Objective: To evaluate the accuracy of Diffusion Weighted MRI in assessment of myometrial invasion and lymph node metastasis in endometrial cancer. Methodology: 30 patients of biopsy-proven endometrial carcinoma was enrolled in this cross-sectional study in the Department of Radiology and Imaging, BSMMU, Dhaka, from March’2021 to February’2023. DW MRI (b-value= 50, 400 and 800 s/mm2) and corresponding ADC map findings were evaluated for presence of myometrial invasion and lymph node metastasis correlating with anatomical T1WI and T2WI in 3.0 Tesla machine taking histopathology as gold standard. Results: Mean age was 60.8±7.2 years with postmenopausal bleeding being the major (76.7%) presenting complaint. Majority (60%) had < 6 months of symptom duration with minimum being 1 month. According to the histological subtype, 70% had endometrioid carcinoma and 26.7 % had serous adenocarcinoma and 3.3% had clear cell carcinoma. In endometrial carcinoma lesions, mean (+ standard deviation) ADC value was (0.719 + 0.601 × 10-3 mm2/s). Sensitivity, specificity, accuracy, positive predictive value and negative predictive value of Diffusion Weighted MRI in determining superficial and deep myometrial invasion were 89.5%, 90%, 90%, 94.45%, 83.35% and 90.9%, 89.5%, 90%, 83.3% & 94.4% respectively. Among 06(20%) patients having lymph node metastasis, 05(83.3%) had deep myometrial invasion and 01(16.7%) had superficial myometrial invasion. In our study, sensitivity, specificity, accuracy, positive predictive value and negative predictive value of Diffusion Weighted MRI in determining lymph node metastasis were 83.3%, 95.8%, 93.3%, 83.3 % and 95.8%. Conclusion: Diffusion Weighted MR Imaging is very accurate and highly specific advanced quantitative tool for assessment of myometrial invasion and lymph node metastasis in the patients of endometrial carcinoma. BJRI, 2024; VOL. 32(2): 112-123